2017
DOI: 10.1590/1678-77572016-0231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resin-modified glass ionomer and topical fluoride on levels of Streptococcus mutans in saliva and biofilm adjacent to metallic brackets

Abstract: Decalcification of enamel during fixed orthodontic appliance treatment remains a problem. White spot lesions are observed in nearly 50% of patients undergoing orthodontic treatment. The use of fluoride-containing orthodontic materials has shown inconclusive results on their ability to reduce decalcification. The aims of this investigation were to compare the levels of Streptococcus mutans (SM) in saliva and biofilm adjacent to orthodontic brackets retained with a resin-modified glass ionomer cement (RMGIC) (Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(74 reference statements)
0
7
0
1
Order By: Relevance
“…Não obstante, outro estudo que foge da linha de pesquisa de plantas medicinas e que entra no âmbito da Ortodontia em Odontologia é o estudo de Andrucioli et al (2017). Em seu estudo, os autores analisaram a capacitação de agregação de biofilme em ionômero de vidro modificado por resina e resina composta quando utilizados na colagem de braquetes ortodônticos, como também houve a análise da eficácia da aplicação tópica de flúor na redução do índice de S. mutans.…”
Section: Resultsunclassified
“…Não obstante, outro estudo que foge da linha de pesquisa de plantas medicinas e que entra no âmbito da Ortodontia em Odontologia é o estudo de Andrucioli et al (2017). Em seu estudo, os autores analisaram a capacitação de agregação de biofilme em ionômero de vidro modificado por resina e resina composta quando utilizados na colagem de braquetes ortodônticos, como também houve a análise da eficácia da aplicação tópica de flúor na redução do índice de S. mutans.…”
Section: Resultsunclassified
“…On the other hand, several clinical studies showed that the fluoride concentrations released in vivo from old GI and RMGI are not high enough to affect the plaque levels of the caries-associated bacteria mutans streptococci and suggested that the antimicrobial activity occurs only in the initial phase and is not responsible for a long-term anti-cariogenic property [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty saliva samples were taken from healthy children by sterile disposable plastic pipette. Saliva samples were taken before breakfast and no tooth cleaning were done by the participants on the sampling days (6) .Participants gave nearly 2 mL samples of unstimulated whole saliva that were collected into sterile test tubes containing 3 ml of brain heart infusion (BHI)broth transport medium. Samples were transported immediately to the laboratory and incubated at 37ºC for 48 hours.…”
Section: I-determination Of the Antibacterial Effects Of Two Pit And ...mentioning
confidence: 99%